2003
DOI: 10.1128/jvi.77.14.8099-8107.2003
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Borna Disease Virus Phosphoprotein Nuclear Localization by the Viral Protein X Encoded in the Overlapping Open Reading Frame

Abstract: Borna disease virus (BDV) is a nonsegmented, negative-strand RNA virus that belongs to the Mononegavirales order. Unlike other animal viruses in this order, BDV replicates and transcribes in the nucleus of infected cells. Therefore, regulation of the intracellular movement of virus components must be critical for accomplishing the BDV life cycle in mammalian cells. Previous studies have demonstrated that BDV proteins are prone to accumulate in the nucleus of cells transiently transfected with each expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
(100 reference statements)
2
30
0
Order By: Relevance
“…We have documented that N contains a bona fide NES that utilizes a CRM1-dependent pathway for traveling through the nuclear pore complex (9). We have also shown that the intracellular distribution of BDV P is influenced by its binding to X, which promotes the cytoplasmic accumulation of P (10). Both BDV X and P contain functional NLS, suggesting that the activity of these signals must be impaired in the context of the X-P complex.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have documented that N contains a bona fide NES that utilizes a CRM1-dependent pathway for traveling through the nuclear pore complex (9). We have also shown that the intracellular distribution of BDV P is influenced by its binding to X, which promotes the cytoplasmic accumulation of P (10). Both BDV X and P contain functional NLS, suggesting that the activity of these signals must be impaired in the context of the X-P complex.…”
Section: Discussionmentioning
confidence: 95%
“…Expression vectors encoding X/P-GFP (pgX/P; GFP is green fluorescent protein), P (pgP) and FLAG-tagged P (pcPF) have been previously described (10). Expression vectors pcPHA and pcXHA encoding hemagglutinin (HA)-tagged P and X BDV proteins, respectively, were generated by subcloning the P and X open reading frames, respectively, into the EcoRI and XhoI sites of plasmid pcDNA3 (Invitrogen, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from these binding studies indicate that X⅐P⅐L and also X⅐P⅐N complexes are formed. Based on immunofluorescence studies of either BDV-infected cells or transfected cells overexpressing X, it was previously suggested that X might act by sequestration of P to the cytoplasm, thereby limiting the availability of P for viral RNA synthesis in the nucleus (30,32). Although translocation of P into the cytoplasm might partially explain the effect of X, our new data suggest that X could also act more directly in the nucleus, namely by association with the viral polymerase complex through binding to P. This interaction would inhibit the formation of functional polymerase complexes by blocking the association of P⅐L with P⅐N⅐RNA complexes or, alternatively, by blocking the gliding process.…”
Section: Discussionmentioning
confidence: 99%
“…The X interaction domain is located between P residues 72 and 87 (30), and the N interaction domain includes P residues 197-201 (24). Co-transfection of pCA-N (encoding BDV-N) reduced luciferase activity some 5-fold (Fig.…”
Section: Identification Of the L-binding Domain In Bdv-p By Mammalianmentioning
confidence: 99%